2013
DOI: 10.1177/0956462413515639
|View full text |Cite
|
Sign up to set email alerts
|

Population-level associations between antiretroviral therapy scale-up and all-cause mortality in South Africa

Abstract: Our aim was to describe the association between increasing access to antiretroviral therapy and all-cause mortality in South Africa from 2005 to 2009. We undertook a longitudinal, population-level study, using antiretroviral monitoring data reported by PEPFAR implementing partners and province-level and national all-cause mortality records from Statistics South Africa (provider of official South African government statistics) to analyse the association between antiretroviral therapy and mortality. Using mixed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…We document gains of 3.1 years in adult life expectancy and 8 years of median length of life in the four years following the introduction of public-sector ART in rural Malawi. Our estimated mortality rates and the change in mortality rate post-ART are similar to published results from the Karonga HDSS in Malawi ( Floyd et al 2010 ; Larson et al 2014 ; Price et al 2016 ) and those of other HDSS sites in Southern and Eastern Africa ( Floyd et al 2012 ).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…We document gains of 3.1 years in adult life expectancy and 8 years of median length of life in the four years following the introduction of public-sector ART in rural Malawi. Our estimated mortality rates and the change in mortality rate post-ART are similar to published results from the Karonga HDSS in Malawi ( Floyd et al 2010 ; Larson et al 2014 ; Price et al 2016 ) and those of other HDSS sites in Southern and Eastern Africa ( Floyd et al 2012 ).…”
Section: Discussionsupporting
confidence: 86%
“…Starting in the early 2000s, access to ART through public-sector programs was greatly improved in SSA. Recent studies have started to document the success of these programs in terms of population-level declines in mortality (both HIV-related and all-cause) in South Africa ( Bor et al 2013 ; Larson et al 2014 ), Malawi ( Floyd et al 2010 ; Jahn et al 2008 ; Price et al 2016 ), and other countries in SSA ( Floyd et al 2012 ; Stoneburner et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Before 2003, most Kenyans had no access to HIV services, but by 2008, 1 in 5 HIV-positive adults were receiving HIV care, with half of those eligible receiving antiretroviral therapy [24]. A South African study found that for every 100 HIV-infected persons on antiretroviral therapy, 6.3 fewer deaths occurred the following year, including among children [25]. Studies in the KEMRI/CDC HDSS showed a halving of all-cause and HIV-specific mortality among young adult females from 2003 to 2009 [26].…”
Section: Discussionmentioning
confidence: 99%
“…The roll out of antiretroviral therapy (ART) in Sub-Saharan Africa led to a decrease in mortality [1]. AIDS-related deaths have fallen by 48% since the peak in 2005 [2].…”
Section: Introductionmentioning
confidence: 99%